Synthesis and crystal structures of transition metal ion complexes of di(2-thienyl)imide. (8th May 2017) - Jiang, Ting; Naik, Tejal K.; Day, Cynthia S.; Noftle, Ronald E.
Graphical abstract: Di(2-thienyl)imide, 1, forms oxygen-bonded complexes with Mn(II), Co(II), and Zn(II).1 can be oxidatively polymerized and has potential as a metal ion uptake and release agent. Abstract: Di(2-thienyl)imide, 1, has been shown to chemically polymerize, and, if metal complexes of 1 could be synthesized, the polymer could have potential applications as an ion sensor and environmental remediation agent. As a first step towards this goal, di(2-thienyl)imide is shown to form complexes with Mn (II), Co (II), and Zn (II) perchlorates. The complexes of Mn 2+ and Co 2+ are isostructural with two di(2-thienyl)imide ligands in equatorial positions and two perchlorate ions axial. The Zn 2+ complex has two water molecules in the axial positions and the thiophene rings in the two equatorial ligands are tilted in the same direction from the median plane due to intra- and intermolecular contacts. The crystal structures and infrared spectra, as well as an improved synthesis and polymerization of di(2-thienyl)imide, are reported and discussed.